Oxidação do corante azul reativo 4 por processos eletroquímicos oxidativos avançados foto-assistidos utilizando ânodos dimensionalmente estáveis - Guimarães, Luciana Silva (2018)
With the increase of extractive activities and consumption of industrialized products, a larger amount of effluents containing organic contaminants, most of them with harmful character to aquatic life, are generated. Among the various existing contaminants, pesticides, drugs, endocrine disruptors etc., the dyes also stand out for their great application, mainly in the textile industry. Among the various existing dyes, in this research, the intention is to study the degradation and mineralization of Reactive Blue 4, which has a toxic, carcinogenic and allergenic character. Based on this environmental concern, researchers have been increasingly dedicated to the development of new technologies with great oxidative power, low cost, which use fewer chemicals to promote the treatment of effluents contaminated by toxic organic compounds. Among the several processes carried out to treat contaminated water, the following ones will be applied and compared in this work: Anodic Oxidation (AO), Electro-Fenton (EF) and Photoelectro-Fenton (PEF), using as electrodes an dimensionally stable anode with composition Ti/Ru0,3Ti0,7O2 and an air diffusion cathode. These processes have as main objective the formation of the hydroxyl radical, which, in contact with the pollutant, has the capacity of oxidize it. Were carried out experiments which evaluated the Reactive Blue 4 color removal by the methods OA, EF and PEF, using as support electrolyte Na2SO4 (0,05 M) and NaCl (0,15 M) singly and also a combination of the two ones (Na2SO4 – 0,025 M; NaCl – 0,075 M); and the mineralization of RB4 by the AO, EF and PEF methods in the presence of Na2SO4 (0,05 M) with the application of different currents (100 and 200 mA). For the color removal, the best results were obtained using NaCl and Na2SO4 as electrolyte, with prominence to AO technique using an electric current of 200 mA. The evaluation of Reactive Blue 4 color removal applying these advanced oxidative electrochemical processes was performed through the technique of molecular absorption spectroscopy in the UV-Vis region. To evaluate the mineralization of the RB4, Total Organic Carbon (TOC) results were obtained, which demonstrated that the best technique was the PEF using 200 mA current. With these parameters applied it was possible to achieve a mineralization of approximately 75% of the amount of initial dye.